Lateralization in 11C‐Metomidate PET and outcome of adrenalectomy in primary aldosteronism. Issue 6 (29th August 2022) - Isojärvi, Juhani; Viukari, Marianna; Pörsti, Ilkka; Leijon, Helena; Vesterinen, Tiina; Seppänen, Marko; Nevalainen, Pasi I.; Matikainen, Niina
Abstract: Introduction: Subtype classification method is essential when considering adrenalectomy as a possible treatment for primary aldosteronism. We aimed to retrospectively evaluate surgical outcomes of primary aldosteronism in patients who had undergone 11 C‐metomidate positron emission tomography ( 11 C‐MTO‐PET) for subtype classification. Methods: Postoperative clinical and biochemical cure and histopathological diagnosis from biobank samples were retrospectively evaluated in 44 patients who had all undergone preoperative 11 C‐MTO‐PET with or without adrenal venous sampling (AVS). We compared those operated based on 11 C‐MTO‐PET alone and those with concordant or discordant lateralization in 11 C‐MTO‐PET and AVS studies according to postoperative immunohistochemical findings and biochemical and clinical cure. Results: Adrenalectomy side was based on 11 C‐MTO‐PET alone in 14 cases and on AVS in 30 cases of whom 42 achieved complete and two partial biochemical cures. Among those who underwent AVS and were operated according to it, the two lateralization methods were concordant in 22 cases and discordant in 8 cases. Similar immunohistochemical profiles and cure rates were seen after 11 C‐MTO‐PET alone or AVS‐based operations. Respectively, those with concordant or discordant 11 C‐MTO‐PET and AVS lateralization did not differ in surgical outcome. Together, we found errors of lateralization diagnostics with 11 C‐MTO‐PET in 18% and with AVS in 3% among those eligible for adrenal surgery. Conclusions: Outcomes of adrenalectomy based on clinically significant lateralization in 11 C‐MTO‐PET alone correspond to those based on 11 C‐MTO‐PET with concordant AVS lateralization. However, our results suggest that diagnosis of unilateral PA should be performed with caution with 11 C‐MTO‐PET in case of discordant lateralization studies. Abstract : We retrospectively analysed 44 adrenalectomized patients with primary aldosteronism who had all undergone preoperative 11 C‐MTO‐PET imaging and had adrenal samples available for histopathological diagnosis. Outcomes of adrenalectomy based on clinically significant lateralization in 11 C‐MTO‐PET alone corresponded to those based on 11 C‐MTO‐PET with concordant AVS lateralization. However, we found errors with 11 C‐MTO‐PET method in 18% of lateralization diagnostics among those eligible for adrenal surgery suggesting caution.